Characteristics of recurrent emergency department visits within 72 hours of visits for the same or related complaints - Sercan Bicakci; Nurcan Bicakci; Ali Duman; Ridvan Atilla (Medicine Science, 2016)
We aimed to investigate the characteristics of recurrent emergency department visits within 72 hours for the same or related complaints. Recurrent visits were defined as any repeated visits to the emergency department within the first 72 hours of discharge after the first admission with the same or similar complaints. The study population included patients revisiting the emergency department within 72 hours after the first visit. Recurrent visit files were screened from the Hospital Information Management System, and data were compared between the first and second visits. Of the 83,578 patients included, 1,952 (2.3%) fulfilled the inclusion criteria. Thus, the revisit rate was 2.3%. Emergency Department triage scores showed no significant differences between the visits, but 2 patients with triage scores of 4 in the first visit subsequently had triage score of 1 in the recurrent visits. In addition, the presence of comorbidities was found to be significantly associated with revisit and hospitalization. Measuring and evaluating the causes of revisits to the emergency department allow assessment of hospital quality. We believe that to reduce the revisit rate, prolonged emergency room observation is necessary, particularly for patients with comorbidities and those presenting complaints related to the cardiovascular system, oncology, and respiratory system. Further, morbidity and mortality rates will consequently decrease. [Med-Science 2016; 5(4.000): 937-40]